KESADARAN POLITIK MASYARAKAT DALAM PEMILIHAN KEPALA DESA DI DESA EELAHAJI KECAMATAN KULISUSU KABUPATEN BUTON UTARA PADA TAHUN 2017 - Eka Suaib; Asriani Asriani; Rahimudin Rahimudin (Universitas Halu Oleo, 2022)
The purpose of this research is to identify and know how the political awareness of the community in the Election of Eelahaji Village Head in 2017. This research uses qualitative method, with data obtained from observations, interviews, and field documentation where informants are determined purposive sampling and using interactive data analysis methods by Miles and Huberman.The results showed that in terms of people's knowledge of Eelahaji village voters about politics, they tended to be enthusiastic to participate in the election of the village head but only follow other communities and didn’t know the importance of politics and rules in organizing elections. In terms of understanding politics, the results showed a low understanding of the electorate about politics due to the lack of willingness of the people themselves to know politics further and the lack of role of local government in providing education about politics. In terms of attitudes towards political phenomena, research shows the tendency of people to continue to accept the practice of Political Money and even view the phenomenon as commonplace and not a serious problem. Meanwhile, in terms of behavior patterns, Eelahaji villagers tend to obey all government directives. In addition, there’s also a polarizing phenomenon among the people of Eelahaji Village during the election